(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Introduction: reading and writing are essential skills in the life and training of children who develop psychomotor, affective, social, and intellectual processes and great interdependence with the environment and the people around them. Objective: to analyze teachers’ conceptions about the process of literacy practices in the initial stage of the school context. Methodology: a questionnaire was applied to 32 Chilean Pre-Basic and Basic teachers in a reading and writing workshop in municipal and subsidized schools in the city of Antofagasta. The responses were collected in written form, with a narrative design organized into three categories: teachers’ beliefs about the acquisition of reading and writing, teaching practices in the teaching process, and the influence of the environment in process mentioned before. Results: conventional methods (synthetic and analytical) have not had significant changes in the teaching of reading and writing; However, technological resources and pedagogical tools have been introduced to strengthen learning, as well as the qualification of its practices. Conclusions: a fundamental role must be assumed in making pedagogical decisions for the selection of specialized material and innovation in literacy methodologies.